Increases in ambient particulate matter air pollution, acute changes in platelet function, and effect modification by aspirin and omega-3 fatty acids: A panel study. Issue 6 (18th March 2016) - Becerra, Adan Z.; Georas, Steve; Brenna, J. Thomas; Hopke, Philip K.; Kane, Cathleen; Chalupa, David; Frampton, Mark W.; Block, Robert; Rich, David Q.
ABSTRACT: Increased particulate matter (PM) air pollutant concentrations have been associated with platelet activation. It was postulated that elevated air pollutant concentrations would be associated with increases in measures of platelet function and that responses would be blunted when taking aspirin and/or fish oil. Data from a sequential therapy trial (30 subjects with type 2 diabetes mellitus), with 4 clinic visits (first: no supplements, second: aspirin, third: omega-3 fatty acid supplements, fourth: aspirin and omega-3 fatty acids) per subject, were utilized. Using linear mixed models, adjusted for relative humidity, temperature, visit number, and season, changes in three platelet function measures including (1) aggregation induced by adenosine diphosphate (ADP), (2) aggregation induced by collagen, and (3) thromboxane B2 production were associated with interquartile range (IQR) increases in mean concentrations of ambient PM2.5, black carbon, ultrafine particles (UFP; 10–100 nm), and accumulation mode particles (AMP; 100–500 nm) in the previous 1–96 h. IQR increases in mean UFP and AMP concentrations were associated with significant decreases in platelet response, with the largest being a –0.43 log(pg/ml) decrease in log(thromboxane B2) (95% CI = –0.8, –0.1) associated with each 582-particles/cm 3 increase in AMP, and a –1.7 ohm reduction in collagen-induced aggregation (95% CI = –3.1, –0.3) associated with each 2097-particles/cm 3 increase in UFP in the previous 72 h. This UFP effect on thromboxane B2 was significantly muted in diabetic subjects taking aspirin (–0.01 log[pg/ml]; 95% CI = –0.4, 0.3). The reason for this finding remains unknown, and needs to be investigated in future studies.